Interannual Differences in Employee Motivation in Manufacturing Enterprises in Slovakia - Kampf, Rudolf; Hitka, Milos; Potkany, Marek (Communications - Scientific letters of the University of Zilina, 2014)
Differences in employee motivation in Slovak manufacturing enterprises during the years 2013 and 2014 are analysed in the paper. Independent samples t-test is used to compare the equality of averages and to calculate the significance level p for individual motivation factors. Definition of the significant increase or decrease of the average level of motivation factors and the comparison of an order of the importance of motivation factors in the year 2013 and 2014 are the findings of the paper. Despite no significant change in various motivation factors they need to be included in the motivation programme of enterprises owing to their importance. Statement that the enterprise management should pay adequate attention to motivation programmes updating because of the interannual changes in employee needs is the research finding. Future development of the level of employee motivation can be predicted following the findings.